CARBON DIOXIDE EMISSIONS IN RETAIL FOOD - Lukić, Radojko; Lalić, Srđan; Sućeska, Azra; Hanić, Aida; Bugarčić, Milica (Economics of Agriculture, 2018)
The analysis of the effects of applying the concept of sustainable development in retail has been attracting interest recently. In that context we have considered greenhouse gases emission in retail. This is achieved by using modern ecological technology in business – through the whole food value chain. The goal is to achieve the planned reductions of carbon dioxide in retail food, which positively reflects the overall performance of food retailers. This empirical research is mainly based on the analysis of the original sustainable reports offcially disclosed by selected food retailers. These reports are now an integral part of the integrated reporting on performance of global food retailers. Having been universally important, harmonized regulations on sustainable retail food reporting are being increasingly applied as a data source for more efficient environmental management. In the future, this will enable the comparative analysis of the carbon dioxide emission of global and other food retailers.